2017
DOI: 10.2147/ott.s143154
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nonsteroidal anti-inflammatory drugs in the incident and recurrent risk of hepatocellular carcinoma: a meta-analysis

Abstract: BackgroundRecent studies have showed that nonsteroidal anti-inflammatory drugs (NSAIDs) could reduce the risk of several types of cancer. However, epidemiological evidence of the association between NSAIDs intake and the risk of hepatocellular carcinoma (HCC) remains controversial.MethodsTo assess the preventive benefit of NSAIDs in HCC, we simultaneously searched the databases of PubMed, EmBase, Web of Science, and Scopus and screened eligible publications.ResultsA total of twelve articles (published from 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 56 publications
1
36
1
Order By: Relevance
“…Although the effect of aspirin on HCC is not well established, 24 this study suggested a potential beneficial effect of aspirin and its interaction with metformin (Table 4).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Although the effect of aspirin on HCC is not well established, 24 this study suggested a potential beneficial effect of aspirin and its interaction with metformin (Table 4).…”
Section: Discussionmentioning
confidence: 69%
“…Therefore, the potential confounding effect of statin and the interaction between metformin and statin should not be neglected. Although the effect of aspirin on HCC is not well established, this study suggested a potential beneficial effect of aspirin and its interaction with metformin (Table ).…”
Section: Discussionmentioning
confidence: 77%
“…Several nationwide cohort studies from Taiwan revealed that the use of concomitant medications with statin and nonsteroidal anti‐inflammatory drugs (NSAIDs) or aspirin could reduce the risk of HCC recurrence in patients receiving curative HCC resection, regardless of HBV status . Recently, a meta‐analysis including 12 studies also demonstrated that NSAIDs significantly reduced the recurrent risk of HCC (HR: 0.79, 95% CI: 0.75‐0.84) . The effects of non‐anti–viral medicine on reduction risk of HCC recurrence should be confirmed through prospective studies or randomised clinical trials.…”
Section: Tertiary Preventionmentioning
confidence: 99%
“…It also plays an important role in preventing cerebrovascular and cardiovascular thrombosis and even lowering the associated mortality, especially in diabetes mellitus patients [7][8][9][10]. Aspirin may also prevent the occurrence of some cancers, such as colorectal cancer [11][12][13][14], lung cancer [15], prostate cancer [16], and head and neck cancer [17], as well as HCC [18]. Its effects are likely due to the inhibition of the cyclooxygenase enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…Aspirin treatment can decrease the occurrence of HCC through the inhibition of the cyclooxygenase enzyme pathway. Some retrospective reports have shown that aspirin decreases the incidence of HCC [18,20]. However, the association between aspirin use and the incidence of HCC has been evaluated only in HBV carriers, not in HCV carriers [21].…”
Section: Introductionmentioning
confidence: 99%